The missing piece of Charlie O'Reilly - Ansari, Rebecca K. S. (New York, NY : Walden Pond Press, an imprint of HarperCollinsPublishers, 2019)
When he keeps insisting that his little brother is missing even though no one else can remember that Liam ever existed, Charlie and his best friend Ana are determined to follow the instructions on a note that may help them find out what happened to Liam.
Keywords: Brothers -- Fiction; Missing children -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Fantasy